DIMENSION OF SEAMOUNT USING MULTIBEAM ECHOSOUNDER IN BENGKULU WATERS - Fahrulian Fahrulian; Henry Manik; Djoko Hartoyo (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
The purpose of this research was to determine the dimensions of seamount using echosuonder in Bengkulu waters. The survey was conducted by BPPT, LIPI, the Ministry of Energy and Mineral Resources, CGGVeritas, and the Institut de Physique du Globe (IPG) Paris in the southwest of the Sumatera island on 18-19 December 2010. Two acoustic instruments were used i.e., ELAC Seabeam 1050D with a frequency of 50 kHz and Simrad EM 12D with a frequency of 12 kHz. Data acquisition was obtained by using the hydrostar software in Baruna Jaya 3 and 4 research vessels. CARIS HIPS and SIPS6.1 softwares were used toprocess the data of bathymetry. Amplitude and backscatter data were obtained by data processing on the MBSystem. Data visualization in 3-D was performed using the Fladermaus 6.2 software (personal license of Djoko Hartoyo). Seamount form was assumed as a cone with an elliptical base to calculate the dimensions. The result showed an under water seamount of 320 Km from the southwest of Bengkulu city at -4°22’9.16’’latitude and 99°25’01.47’’ longitude. The seamount height was ± 3,968 meters and had two peak separated at ± 3,050 meters. Seamount peaks located at ± 1.270 meters below sea level. The major axis was ± 50,240 meters and the minor axis in this seamount was ± 5,644 meters Keywords: seamount dimension, bathymetry, backscattering, Bengkulu Waters